AFRICAN VULTURE OPTIMIZED INTEGRATED CONTROL TECHNIQUE FOR PV-FED OPEN-END WINDING INDUCTION MOTOR PUMP APPLICATION (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2024)
Open-end winding induction motors (OEWIM) have gained much attention, and they are used for solar photovoltaic (PV) fed pumping applications as a compromise alternative to multi-level inverters. Solar irradiance conditions further exacerbate the nonlinear control problem, resulting in significant loss of power and low reliability, which affects motor operation. To overcome these issues, this paper presents an optimized integrated control technique-based PV integrated three-level dual inverter fed Open-end winding induction motors for pumping application. An integrated African vulture optimization algorithm and scalar coupled pulse width modulation (AVO-SCPWM) based control techniques are proposed to extract the maximum power from the solar PV source and control the induction motor pump. Here, the AVO-based maximum power point tracking (MPPT) technique adjusts the modulation index (ma) by insolation and temperature. The proposed technique balances the zero-sequence current, reduces THD, and reduces the switching losses over the inverter. The proposed work is evaluated in MATLAB/Simulink software and compared with the existing conventional induction motor (IM), Conventional OEWIM Drive, and scalar decoupled PWM-based IM techniques under two climatic conditions. Thus, the simulation results demonstrate that the proposed technique accomplishes better than the existing techniques.
Keywords: Open-end winding induction motors; Photovoltaic; Scalar coupled pulse with modulation (PWM); African vulture optimization; Dual inverter; Maximum power point tracking (MPPT); Total harmonic distortion (THD)